Exploration of Analyte Electrolyticity Using Multi-SRR-Hexagonal DNG Metamaterials and ZnO Thin Films - Defrianto, Defrianto; Saktioto, Saktioto; Rini, Ari Sulistyo; Syamsudhuha, Syamsudhuha; Anita, Sofia; Soerbakti, Yan (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2025)
Advanced engineered metamaterials (MTMs) significantly contribute to modern technological advancements, particularly through hybridization with semiconductor materials like zinc oxide (ZnO), which enhance sensor sensitivity and performance. This study aims to investigate the optical properties of hybrid MTMs and develop a novel sensor medium capable of detecting early electrolytic behaviors of analytes. Utilizing the finite-difference time-domain (FDTD) method, the sensor was designed, characterized, and integrated, featuring a hexagonal multi-cell split ring resonator (SRR) structure coated with a 200-nm ZnO thin film. The geometry of the SRR MTM was optimized using a modified Nicolson-Ross-Weir electromagnetic field function method. Results demonstrate that the MTM exhibits double-negative optical characteristics with a performance index reaching 102. Moreover, the sensor presents dual-band resonance frequencies for reflection and transmission attributed to the combination of the multi-SRR hexagonal design and ZnO coating, with an absorption peak at 8.71 GHz. Testing the sensor in varying electrolytic conditions, such as seawater, revealed a measurable reduction in resonance depth and increased sensitivity, characterized by a frequency shift of 5.25 MHz per 0.7 S/m increment in electrical conductivity. These findings highlight the MTM sensor's potential as an effective tool for enhancing spectrum readout accuracy and sensitivity in analyte detection applications.